Diversity and Composition of Bacterial Community in Soils and Lake Sediments from an Arctic Lake Area - Wang, Neng Fei; Zhang, Tao; Yang, Xiao; Wang, Shuang; Yu, Yong; Dong, Long Long; Guo, Yu Dong; Ma, Yong Xing; Zang, Jia Ye (Frontiers in Microbiology, 2016)
This study assessed the diversity and composition of bacterial communities within soils and lake sediments from an Arctic lake area (London Island, Svalbard). A total of 2,987 operational taxonomic units were identified by high-throughput sequencing, targeting bacterial 16S rRNA gene. The samples from four sites (three samples in each site) were significantly different in geochemical properties and bacterial community composition. Proteobacteria and Acidobacteria were abundant phyla in the nine soil samples, whereas Proteobacteria and Bacteroidetes were abundant phyla in the three sediment samples. Furthermore, Actinobacteria, Chlorobi, Chloroflexi, Elusimicrobia, Firmicutes, Gemmatimonadetes, Nitrospirae, Planctomycetes, Proteobacteria significantly varied in their abundance among the four sampling sites. Additionally, members of the dominant genera, such as Clostridium, Luteolibacter, Methylibium, Rhodococcus, and Rhodoplanes, were significantly different in their abundance among the four sampling sites. Besides, distance-based redundancy analysis revealed that pH (p < 0.001), water content (p < 0.01), ammonium nitrogen (NH4+-N, p < 0.01), silicate silicon (SiO42--Si, p < 0.01), nitrite nitrogen (NO2--N, p < 0.05), organic carbon (p < 0.05), and organic nitrogen (p < 0.05) were the most significant factors that correlated with the bacterial community composition. The results suggest soils and sediments from a lake area in the Arctic harbor a high diversity of bacterial communities, which are influenced by many geochemical factors of Arctic environments.